1985
DOI: 10.1111/j.1744-313x.1985.tb00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Distribution of the Pk Antigen as Determined by a Monoclonal Antibody

Abstract: SUMMARY Using an anti‐Pk monoclonal antibody (mAb) designated CPK‐1, the expression of the Pk antigen was assessed on normal human tissue from non‐Pk individuals. Although the Pk antigen was detected on fibroblasts and blood vessels as previously reported, it was also found on smooth muscle cells of the digestive tract and the urogenital system. Pk was also found on glandular cells of the stomach, oesophagus and prostate. Additionally, CPK‐1 reacted weakly with oesophagus squamous cells, and a small number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…Gb3 is the pK blood group antigen (34). Tissue surveys using anti-PK antisera have shown that human ovaries do not express this glycolipid (35). Our data are consistent with this finding: low levels of Gb3 were detected in some "normal" ovarian tissue, but the levels were markedly elevated in the ovarian tumor tissue samples.…”
Section: Methodssupporting
confidence: 81%
“…Gb3 is the pK blood group antigen (34). Tissue surveys using anti-PK antisera have shown that human ovaries do not express this glycolipid (35). Our data are consistent with this finding: low levels of Gb3 were detected in some "normal" ovarian tissue, but the levels were markedly elevated in the ovarian tumor tissue samples.…”
Section: Methodssupporting
confidence: 81%
“…This mutant was shown to display elevated sensitivity to serum-mediated killing. Further, the P k epitope is also present on the surface of erythrocytes and several epithelial cell types (79), and because of this immunochemical identity, no naturally occurring antibodies toward the P k epitope of M. catarrhalis LOS are likely to be present in human serum. Loss of the P k epitope then apparently results in the exposure of a different LOS epitope and, subsequently, to the activation of the complement system (156).…”
Section: Losmentioning
confidence: 99%
“…These data suggest that resistance to serum complement-mediated killing may be related to the presence of the two terminal galactose residues on the LOS. These residues form part of a structure that has been shown to be immunochemically identical to the P k (Gal␣1-4Gal␤1-4Glc) antigen found on a number of human cells including erythrocytes, as well as gastrointestinal, ureteral, and bladder epithelial cells (7,29,35). It would appear that the Moraxella Gal␣1-4Gal␤1-4Glc structure may act as a human self-antigen and that antibodies to it are not present in normal human serum.…”
Section: Discussionmentioning
confidence: 93%